EVALUATING THE IMPACT OF MOTIVATION FACTORS ON EMPLOYEE ORGANIZATIONAL BEHAVIOR USING THE PIPRECIA S METHOD - JANOŠIK, Marija; ĐUKIĆ, Tijana; MLADENOVIĆ, Marija (Journal of process management and new technologies, 2024)
Motivation, as a key determinant of productivity, seeks to provide reciprocal benefit by satisfying both the worker's and the organization's requirements. The advent of globalization and rapid economic progress has presented novel issues in motivation and productivity. Organizations aim to address these rapid changes by seeking novel approaches to enhance motivation in their work environment, necessitating managers to exhibit creativity and innovation in devising and executing tactics to boost motivation. To attain the intended outcome, managers must identify the variables that lead to a decrease in motivation and devise strategies to eliminate or counteract these problems by incorporating positive elements that promote motivation. Motivation is a multifaceted process, as various aspects that drive motivation do not have the same impact on everyone. In other words, what motivates one person may not have the same effect on another one. This research aims to analyze the impact of motivation on employees' organizational behavior. The objective of the study is to ascertain the specific incentives that exert a favorable influence on organizational behavior, ultimately resulting in enhanced employee productivity.